Genes for Glycosylphosphatidylinositol Toxin Biosynthesis in Plasmodium falciparum - Delorenzi, Mauro (American Society for Microbiology, 2002)
About 2.5 million people die of Plasmodium falciparum malaria every year. Fatalities are associated with systemic and organ-specific inflammation initiated by a parasite toxin. Recent studies show that glycosylphosphatidylinositol (GPI) functions as the dominant parasite toxin in the context of infection. GPIs also serve as membrane anchors for several of the most important surface antigens of parasite invasive stages. GPI anchoring is a complex posttranslational modification produced through the coordinated action of a multicomponent biosynthetic pathway. Here we present eight new genes of P. falciparum selected for encoding homologs of proteins essential for GPI synthesis: PIG-A, PIG-B, PIG-M, PIG-O, GPI1, GPI8, GAA-1, and DPM1. We describe the experimentally verified mRNA and predicted amino acid sequences and in situ localization of the gene products to the parasite endoplasmic reticulum. Moreover, we show preliminary evidence for the PIG-L and PIG-C genes. The biosynthetic pathway of the malaria parasite GPI offers potential targets for drug development and may be useful for studying parasite cell biology and the molecular basis for the pathophysiology of parasitic diseases.